Given log3(3b + 1) - log3(a-2) = -1 for a > 2. Express b in terms of a.

We can start by recognising one of our properties of log. That is loga(x) - loga(y) = loga(x/y). Performing this on our question we get: log3((3b+1)/(a-2)) = -1. Now we can remove our log and rewrite our equation as follows: (3b+1)/(a-2) = 3-1 implying that (3b+1) = (a-2)/3 implying that 3b = (a-2)/3 - 1 or better, inserting the -1 into our fraction and getting (a-5)/3. Finally implying that b = (a-5)/9.

Answered by Jason W. Maths tutor

14124 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How do you find the normal to a curve at a given co-ordinate?


Given that y=((4x+1)^3)sin2x. Find dy/dx.


Why is the derivative of sin(x), cos(x)?


Mechanics (M1): Particle moving on a straight line with constant acceleration (Relationships of the 5 Key Formulae)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences